Beyond belief - Mackay, Hugh, 1938- (Sydney, New South Wales : Pan Macmillan, 2016)
What do people actually mean when they say 'God'? Around two-thirds of us say we believe in God or some 'higher power', but fewer than one in ten Australians attend church weekly. In Beyond Belief, Hugh Mackay presents this discrepancy as one of the great unexamined topics of our time. He argues that while our attachment to a traditional idea of God may be waning, our desire for a life of meaning remains as strong as ever. Mackay interviews dozens of Australians representing many different points on the spectrum of faith, including some who are part of the emerging 'spiritual but not religious' movement. He exposes the deep vein of ambivalence about religion that runs through our society: we may not actively worship, but we still like to see local churches operating in our midst, and we use 'our' church to marry, christen our babies, educate our children and commemorate our dead. He points out some uncomfortable truths, such as our tendency to call on God only in a crisis, and unpacks our human need for 'answers', even when science can't find them. He endorses the Christian ideal of the good life -- a life lived for others -- but acknowledges that there are many pathways to that same goal, not all of them religious. Written with all the insight and compassion we have come to expect of our leading chronicler of Australian life, Beyond Belief is an engrossing exploration of the ways we find spiritual fulfilment in an avowedly secular age.
Introduction: religion goes marching on -- Born to believe -- Why religion will survive and prosper -- Anyone for church? -- SBNR -- Reasonable faith -- When we say 'God'... -- Proving the existance of which God? -- Beyond belief -- Love is enough.
Library's N copy signed by Hugh Mackay, 6 June 2017.
"How we find meaning, with or without religion" -- Cover.
Includes bibliographical references (pages 259-266) and index.
Keywords: Belief and doubt; Faith; Trust in God; Spiritual life; Belief and doubt; Faith; Spiritual life; Trust in God; Australian